Legal and Institutional Bases of Functioning of the Eurasian Union - V. M. Malinovskaya (MGIMO University Press, 2012)
In present article are investigated a modern condition and tendencies of development of the Eurasian economic integration. In these purposes the analysis legal and institutional bases of functioning of the Eurasian union which participants at the present moment are the Republic Belarus, the Republic of Kazakhstan and the Russian Federation will be carried out. In article the author allocates some problems of customs regulation in the Eurasian union.